Child Social Media Influencers and Unhealthy Food Product Placement - Alruwaily, Amaal; Mangold, Chelsea; Greene, Tenay; Arshonsky, Josh; Cassidy, Omni; Pomeranz, Jennifer L; Bragg, Marie (Pediatrics (Evanston), 2020)
We aimed to determine the frequency with which kid influencers promote branded and unbranded food and drinks during their YouTube videos and assess the nutritional quality of food and drinks shown. Researchers used Socialbakers data to identify the 5 most-watched kid influencers (ages 3 to 14 years) on YouTube in 2019. We searched for 50 of their most-watched videos and 50 of their videos that featured food and/or drinks on the thumbnail image of the video. We coded whether kid influencers consumed or played with food or toys, quantified the number of minutes food and/or drinks appeared, and recorded names of branded food and/or drinks. We assessed the nutritional quality of foods using the Nutrient Profile Model and identified the number of drinks with added sugar. A sample of 418 YouTube videos met the search criteria, and 179 of those videos featured food and/or drinks. Food and/or drinks were featured in those videos 291 times. Kid influencers' YouTube videos were collectively viewed >48 billion times, and videos featuring food and/or drinks were viewed 1 billion times. Most food and/or drinks were unhealthy branded items ( = 263; 90.34%; eg, McDonald's), followed by unhealthy unbranded items ( = 12; 4.1%; eg, hot dogs), healthy unbranded items ( = 9; 3.1%; eg, fruit), and healthy branded items ( = 7; 2.4%; eg, Yoplait yogurt). Kid influencers generate millions of impressions for unhealthy food and drink brands through product placement. The Federal Trade Commission should strengthen regulations regarding product placement on YouTube videos featuring young children.